ESTABLISHING COMMUNICATION NETWORK MANAGEMENT AMONG THE ISLAMIC UNIVERSITY LIBRARY IN WEST JAVA - Yunus Winoto (Metakom, 2018)
Through the provision of information resources, both printed materials and electronic forms are expected to meet the needs of the academic community of the institution, so that the role of the college library as "the hearts of educational programs" can be realized. Nevertheless, attempts to meet the information needs of the many and diverse library user libraries are not an easy task. Moreover, often the user has a high desire for the completeness and availability of the collection and this is often a problem and also the challenge of most library managers, especially college libraries. It is also felt by the managers of the library of Islamic universities in West Java like UIN Sunan Gunung Jati Bandung, IAIN Syeh Nurjati Cirebon and some other Islamic college libraries in West Java. One effort to address this need to be cooperation with libraries and other information centers to share information. In this communication communication perspective is a form of communication network. The mixed method is a strategy that uses quantitative and qualitative research in one study. Keywords: Communication network, library cooperation, college library.